Implementation Of A Data-Based Planning (PBD) Program In Improving The Quality Of Educators And Educational Personnel (Case Study At SMA Negeri 1 Tuban) - Oktody, Wahyu; Nurabadi, Ahmad; Zulkarnain, Wildan (Proceedings Series of Educational Studies, 2024)
Improving the quality of education is one of the main focuses in developing the national education system. The PBD program emerged as an innovative solution that integrates the use of data in the educational planning process. This research aims to: (1) determine the process of implementing the Data Based Planning (PBD) program at SMA Negeri 1 Tuban, (2) determine the obstacles faced in the process of implementing the Data Based Planning Program (PBD) at SMA Negeri 1 Tuban, (3) determine the impact of implementing the Data Based Planning (PBD) program on the quality of educators and education staff at SMA Negeri 1 Tuban. The approach used in this qualitative research is a case study type of research. The informants in this research were the school principal, deputy head of curriculum, teachers, school operators, and students of SMA Negeri 1 Tuban. Data collection used in this research was interview, observation and documentation techniques. Based on the data analysis that has been carried out, the following research results were obtained: (1) the implementation of the PBD program was carried out through a series of activities which included PBD socialization activities from education and school offices, simulation activities and AN rehearsals, implementation of AN activities, downloading and understanding the results of report cards. education, IRB activities based on education report cards, formulation of school activities in the form of RKT and RKAS based on education report cards, approval from all parties related to the RKT and RKAS that have been determined; (2) Obstacles during implementation include the implementation of AN where there are problems with the server, types of questions that are not relevant, random selection of students which is less relevant in describing the competency of all students, and the time for preparing the RKT and RKAS coincides with other school activity schedules; (3) the impact of the implementation of the PBD program felt by schools includes improvements to the school planning process as well as improvements to the quality of educators and school education staff. Keywords: Program Implementation, Data Based Planning (PBD), Quality of Educators and Education Personnel.